THE EFFECT OF COMPANY SIZE, ASSET GROWTH AND ASSET STRUCTURE ON CAPITAL STRUCTURE IN THE TEXTILE AND GARMENT INDUSTRY OF THE INDONESIA STOCK EXCHANGE - Akbar, Jufri Sani; Nadia Sri Rezeki (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The Textile and Garment Industry is an industry that makes a significant contribution to economic growth in Indonesia, making a large contribution to the PDP (Gross Domestic Product), then the reason in this study is how company size, asset growth and asset structure can affect capital structure. Research with 12 samples of textile and garment companies listed on the IDX with data from 2020 - 2024 using the purposive sampling method. Pecking order theory is the choice because the use of funding sources refers to internal funds, debt, and equity. The analysis method uses parametric statistics panel data regression with variable measurement assumptions. The results of the regression analysis obtained the results that the R-squared was 0.666565 and the Adjusted R-squared was 0.558424, and this is evident from the results of hypothesis testing both simultaneously and partially there is an influence of company size, asset growth and asset structure on capital structure. Keywords: Company Size, Asset Growth, Asset Structure and Capital Structure